Birth of the First Thai Native Cross-bred Foal Through Artificial Insemination with Frozen Semen - Kanittha Phetudomsinsuk; Anuchai Pinyopummin; Piyawan Suthunmapinanta; Kornchai Kornkaewrat; Aree Laikul; Kaitkanoke Sirinarumitr (Agriculture and Natural Resources, 2010)
Horse breeding has benefited widely from the use of frozen semen. This study investigated the usefulness of artificial insemination in the Thai native crossbred horse breed in order to increase reproductive success and improve breeding management and the genetics of the equine population in Thailand. Semen, collected from a 7-year-old Thai native crossbred stallion was frozen using the liquid nitrogen vapor freezing method. An insemination dose of 50 × 106 motile cells frozen semen was used in one intrauterine artificial insemination and resulted in the pregnancy and birth of the first healthy Thai native crossbred offspring.